Analisis Kredibilitas Endorser, Kreativitas Iklan terhadap Efektivitas Iklan AXIS Siap Kaya Mendadak versi Tukang Ojek dan Brand Awareness AXIS di Pekanbaru - Rahmat Setiawan; Jushermi '; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is conducted to analyze comprehensive influences between Endorser Credibility and Advertising Creativity as exogenous constructs towards Advertising Effectiveness of “AXIS Siap Kaya Mendadak versi Tukang Ojek” and Brand Awareness of AXIS in Pekanbaru as endogenous construcs. There are four latent variables in this research such as Endorser Credibility (X1), Advertising Creativity (X2), Advertising Effectiveness (Y1) and Brand Awareness (Y2). There are 237 respondents in this study which are chosen by quota-area sampling from all Pekanbaru citizens as total population and data are taken by giving them structural questionaires. Meanwhile, Structural Equation Modeling (SEM) method are chosen for data analysis by AMOS version 21. The result of this research shows that Advertising Creativity and Effectiveness of “AXIS Siap Kaya Mendadak versi Tukang Ojek” affect both positively and significantly towards Brand Awareness of AXIS in Pekanbaru. On the context of affecting Brand Awareness, Advertising Creativity takes greater effect than its Effectiveness. Moreover, Advertising Creativity is also affecting Advertising Effectiveness of “AXIS Siap Kaya Mendadak versi Tukang Ojek” both positively and significantly. Meanwhile, Endorser Credibility is the only affecting variable to Advertising Creativity, but it doesn’t affect either Advertising Effectiveness of “AXIS Siap Kaya Mendadak versi Tukang Ojek” or Brand Awareness of AXIS in Pekanbaru.Keywords: Endorser Credibility, Advertising Creativity, Advertising Effectiveness, Brand Awareness